Searching and selecting the best evidence efficiently: a tool for clinicians, professors and dental students - Paulo NADANOVSKY (RGO: Revista Gaúcha de Odontologia, 2018)
The aim of this article was to offer an efficient systematic search strategy appropriate for clinicians, professors and dental students, for when they have a question regarding the effectiveness of clinical intervention. We adapted the “6-S System” proposed for Medicine in order to build a search strategy focused on oral health, which is speedy, easy to use and arrives at the appropriate evidence. With a focus on validity and search efficiency, the following searching sequence is proposed: critical abstracts of systematic reviews (SR) of randomized controlled trials (RCTs), SR of RCTs, critical abstracts of RCTs, and RCTs. These can be searched in the Cochrane library; evidence-based journals; websites and blogs; and in Pubmed using the tool Clinical Queries. This strategy can enhance the ability to quickly retrieve evidence that is important to dental education, clinical practice and delivery of oral health care. The adoption of strategies such as the one proposed in this paper is likely to increase evidence based dental practice.